2021
DOI: 10.1128/msystems.00385-21
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Viruses Carrying Genes for Microbial Extremotolerance in the Atacama Desert Hyperarid Soil

Abstract: Viruses play an essential role in shaping microbial community structures and serve as reservoirs for genetic diversity in many ecosystems. In hyperarid desert environments, where life itself becomes scarce and loses diversity, the interactions between viruses and host populations have remained elusive. Here, we resolved host-virus interactions in the soil metagenomes of the Atacama Desert hyperarid core, one of the harshest terrestrial environments on Earth. We show evidence of diverse viruses infecting a wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 104 publications
(150 reference statements)
0
26
0
Order By: Relevance
“…The relatively low species richness, broad range and steep gradients of geochemical variables promise more straight-forward establishment of ecological patterns and underlying mechanisms. The diversity and community dynamics of viruses in extreme environments such as the Atacama Desert 17 , cryosphere 18 , 19 , acid mine drainage (AMD) environment 20 , 21 , and Earth’s subsurface 7 , 22 , 23 have recently been investigated through meta-omics approaches; yet, extensive sampling and analysis of viral communities across large geographic scales to resolve their ecological distribution patterns and drivers have not been conducted. Here we strive to address this knowledge gap by utilizing a massive metagenomic data set generated from 90 AMD sediments sampled across Southern China (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low species richness, broad range and steep gradients of geochemical variables promise more straight-forward establishment of ecological patterns and underlying mechanisms. The diversity and community dynamics of viruses in extreme environments such as the Atacama Desert 17 , cryosphere 18 , 19 , acid mine drainage (AMD) environment 20 , 21 , and Earth’s subsurface 7 , 22 , 23 have recently been investigated through meta-omics approaches; yet, extensive sampling and analysis of viral communities across large geographic scales to resolve their ecological distribution patterns and drivers have not been conducted. Here we strive to address this knowledge gap by utilizing a massive metagenomic data set generated from 90 AMD sediments sampled across Southern China (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In general, viral diversity in extreme environments is still largely unexplored ( 26 , 27 ). In comparison to other hyperarid and saline environments, i.e., the Atacama Desert ( 28 , 29 ) and the Peñahueca shallow saline lake ( 30 ), a relatively high number of vOTUs was detected in the Aral Sea basin. Viruses that were linked to distinct hosts contained auxiliary metabolic genes (AMGs) that may play roles in the biogeochemical cycles, competitiveness, and resilience against environmental stress of their putative hosts.…”
Section: Discussionmentioning
confidence: 83%
“…It was also suggested that the lysogenic lifestyle is predominant in harsh environments ( 36 ). In a recent study of the viral community in the Atacama Desert, Hwang and colleagues ( 29 ) suggested that under less favorable conditions, viruses likely undergo lysogeny cycles to seek protection in their host cells as a survival strategy. In the present study, the area that dried out 5 years ago was the soil zone that was nearest to the present shoreline of the Aral Sea and can be considered a hostile environment for most organisms due to its high salinity ( 3 ) compared to other sampling areas.…”
Section: Discussionmentioning
confidence: 99%
“…Additional MAGs that were excluded in the dRep process due to low quality in CheckM but had good contamination/completeness scores in uBin and formed their own cluster in the dRep compare mode were additionally considered for k-mer based virus-host linkages. Viral scaffolds were assigned to these MAGs using VirusHostMatcher 119 at a d2* threshold of 0.3, as previously performed 120 . Spacer-protospacer interactions and virus-host interactions based on k-mers were visualized using Cytoscape v.3.9 106 .…”
Section: Methodsmentioning
confidence: 99%